Comparison of early clinical outcomes between CR and PS prostheses in total knee arthroplasty for rheumatoid arthritis patients - a retrospective cross-sectional study - Ding, Haoyuan; Han, Dapeng; Ma, Nanshan; Gao, Chenxin; Yao, Jie; Ouyang, Guilin (Frontiers in Surgery, 2025)
ObjectiveTo compare the early clinical outcomes of posterior cruciate ligament-retaining (CR) and posterior stabilized (PS) knee prostheses in total knee arthroplasty for patients with rheumatoid arthritis.MethodsA retrospective analysis was conducted on 74 patients with rheumatoid arthritis (RA) who underwent unilateral total knee arthroplasty (TKA) from January 2021 to December 2022. Among these, 39 patients received CR prostheses (CR group), while 35 received PS prostheses (PS group). Data on operation time, intraoperative blood loss, hospital stay, preoperative and postoperative Visual Analogue Scale (VAS) scores, American Knee Society Score (AKSS), Functional Joint Score-12 (FJS-12) scores, Health Assessment Questionnaire scores (HAQ) and postoperative complications were recorded and compared between the two groups.ResultsAll 74 patients successfully completed the surgery without complications. The average operation time for the CR group was shorter than that of the PS group, with no statistically significant differences in intraoperative blood loss or hospital stay. Both groups showed improved postoperative AKSS scores, VAS scores, and HAQ Scores compared to preoperative levels. Between-group comparisons showed no statistical differences in postoperative AKSS, VAS, HAQ scores. However, the CR group had significantly higher FJS-12 scores at 6 and 12 months postoperatively compared to the PS group.ConclusionBoth CR and PS prostheses can achieve good clinical outcomes in TKA for RA patients. Compared to PS prostheses, CR prostheses may provide better knee proprioception postoperatively, as indicated by higher FJS-12 scores at 6 and 12 months postoperatively.